Seed Transmission of Pseudoperonospora cubensis - Cohen, Yigal (Public Library of Science, 2014)

(untitled)
Pseudoperonospora cubensis, an obligate biotrophic oomycete causing devastating foliar disease in species of the Cucurbitaceae family, was never reported in seeds or transmitted by seeds. We now show that P. cubensis occurs in fruits and seeds of downy mildew-infected plants but not in fruits or seeds of healthy plants. About 6.7% of the fruits collected during 2012–2014 have developed downy mildew when homogenized and inoculated onto detached leaves and 0.9% of the seeds collected developed downy mildew when grown to the seedling stage. This is the first report showing that P. cubensis has become seed-transmitted in cucurbits. Species-specific PCR assays showed that P. cubensis occurs in ovaries, fruit seed cavity and seed embryos of cucurbits. We propose that international trade of fruits or seeds of cucurbits might be associated with the recent global change in the population structure of P. cubensis.